(untitled) (Journal of Atomic and Molecular Sciences, 2017)
Diphenyl disulfide (DPDS) finds a wide range of applications in organic synthesis, polymer manufacture, and other fields. The structure of the DPDS molecule makes it amenable to monitor by Raman spectroscopy. Studying the fate of DPDS in the course of chemical reactions is of great significance for delineating mechanisms. In this work, the normal Raman and surface-enhanced Raman spectroscopy (SERS) signals of DPDS in ethanol solution have been characterized. In ethanol solution, the Raman signals of DPDS are completely obscured by the solvent signal. However, after irradiation for more than 10 s, a characteristic peak of DPDS appears at ν=2544 cm^-1 (in both normal Raman and SERS), and a further peak at ν=1582 cm^-1 appears in the SERS spectrum. Hence, in situ measurement and monitoring of DPDS in ethanol solution by SERS is feasible. It would allow us to reveal the micro mechanisms of chemical reactions, determine kinetic characteristics, estimate reasonable reaction end points, improve reaction selectivity, assess the quality and yield of the product, and so on.